RELEVANSI SUASANA KELAS YANG DICIPTAKAN GURU FISIKA DALAM PENGEMBANGAN KECERDASAN SOSIAL DAN EMOSIONAL SISWA - ., Ni Kadek Vingki Aryanti; ., Prof. Dr. I Wayan Santyasa,M.Si; ., Putu Artawan, S.Pd. (Jurnal Pendidikan Fisika Undiksha, 2016)
Penelitian ini bertujuan untuk mendeskripsikan suasana kelas yang diciptakan guru fisika, kecerdasan sosial dan emosional siswa, serta relevansi suasana kelas yang diciptakan dalam mengembangkan kecerdasan sosial dan emosional. Peneliti menggunakan pendekatan kualitatif dimana 12 siswa dan satu guru fisika dipilih sebagai informan. Data dikumpulkan dengan teknik observasi, wawancara, triangulasi dan dokumentasi. Lalu dianalisis dengan beberapa tahapan yaitu reduksi data, penyajian data dan verifikasi. Setelah analisis data, peneliti menemukan hasil sebagai berikut. 1) Suasana kelas yang diciptakan guru cenderung kurang edukatif, terkontrol dan otoriter. 2) Aspek kecerdasan sosial siswa yang muncul belum optimal dimana empati siswa masih tahap kognitif, sehingga aspek kecakapan sosialnya masih berada pada tahap dasar. 3) Aspek kecerdasan emosional yang dominan muncul adalah kesadaran diri dan pengelolaan emosi yang negatif, sedangkan aspek yang tidak dominan muncul adalah integritas dan adaptabilitas diri. 4) Suasana kelas yang kiranya mendukung pengembangan kecerdasan sosial dan emosional adalah suasana yang safe and care tetapi tetap menantang melalui kegiatan yang melibatkan siswa secara aktif ditambah pemberian nasihat, motivasi, humor dan reward.Kata Kunci : kecerdasan emosional, kecerdasan sosial, safe and care, suasana kelas. This study aimed at describing the classroom atmosphere, social intelligence, emotional intelligence, and the relevance of classroom atmosphere in developing the students’ social and emotional intelligences. The researcher used qualitative approach. 12 students and one physics teacher were selected as informant. Data were collected by means of observation, interviews, triangulation, and documentation, and then were analyzed with these following steps: data reduction, presentation, and verification. After analyzing the data, the researcher finds the results as follows. 1) The classroom atmosphere created by teachers tends to be less educative, less controlled and authoritative. 2) The aspects of social intelligence that appeared are not optimized. Students’ empathies are still at cognitive stage, so the intelligence aspect of the students is still at basic stage. 3) The emotional intelligence of students tends to be good in recognizing This study aimed at describing the classroom atmosphere, social intelligence, emotional intelligence, and the relevance of classroom atmosphere in developing the students’ social and emotional intelligences. The researcher used qualitative approach. 12 students and one physics teacher were selected as informant. Data were collected by means of observation, interviews, triangulation, and documentation, and then were analyzed with these following steps: data reduction, data display, and verification. After analyzing the data, the researcher finds the results as follows. 1) The classroom atmosphere created by teachers tends to be less educative, less controlled and authoritative. 2) The aspects of social intelligence that appeared are not optimized. Students’ empathies are still at cognitive stage, so the intelligence aspect of the students is still at basic stage. 3) The aspect of emotional intelligence that often appeared are self-awareness and managing negative emotions, while the aspect that not appeared are integrity and self-adaptability. 4) The classroom atmosphere which support the development of social and emotional intelligence is the atmosphere which is safe and care but challenge through the activities which involve the students actively, and give advice, motivation, joke, and reward to the students.keyword : emotional intelligence, social intelligence, safe and care, the classroom atmosphere